Anti diabetic activity of Cynodon dactylon Linn In streptozotocin induced Diabetic Rats and its comparison with some standard flavonoids - Garg, Naveen; Bhargava, Amit (Asian Journal of Pharmaceutical Research and Development, 2023)
The aim of present investigation is to evaluate Antidiabetic activity of hydroalcohol extract of whole plant of cynodon dactylon Linn. In streptozotocin induced diabetic rats. Treatment with Cynodon dactylon hydro alcohol extract at two different dose 200 mg/kg and 400 mg/kg and its comparison with standard drug gilbencLinnide at dose of 5 mg/g and some flavonoids i.e. quercertin, kaempferol and epicatichin each at dose of 100mg/kg for 15 days, after induction of diabetes by streptozotocin 50 mg/kg , caused significant decrease in level of tri glycerides, total cholesterol and significantly increase in level of HDL and body weight compared to disease control group. It is furthermore Cynodon dactylon Linn at dose of 200mg/kg and 400mg/kg shows more significant result than some of standard flavonoids. Thus, whole plant of Cynodon dactylon Linn. may have potential Antidiabetic agent.